(untitled) (Eurasian Scientific Herald, 2023)
This article provides information on the antecology and seed biology of the false chestnut (Aesculus hippocastanum L), the formation of seeds enclosed in a longitudinal fruit capsule, and its biological structure and benefits for human life.